PEMANFAATAN KARBON AKTIF DARI BATUBARA KOTOR (DIRTY COAL) SEBAGAI ADSORBEN ION LOGAM Cd 2+ DAN Pb 2+ DALAM LARUTAN - Yogie Henry Payung; Saibun Sitorus; Alimuddin - (JURNAL KIMIA MULAWARMAN, 2014)
The research of activated carbon utilization of dirty coal as an adsorbent ion cadmium (Cd) and plumbum (Pb) has been done. In this research, the variations of solutions pH value (1, 2, 3, 4, 5 and 6), contact time (5, 10, 15, 30, 45, 60, 75 and 90 minutes), and the variation of concentration (20, 40, 60, 80 and 100 mg/L) were applied. The determination of cadmium and plumbum ion concentraction used an Atomic Absorption Specthrometer (AAS). The optimum condition cadmium ion on pH 4, than in the plumbum on pH 5 with optimum time contact is 15 minutes and the maximum adsorptive capacity cadmium ion in value is 2,90 mg/g, than on plumbum ion is 3,08 mg/g.Keywords: Adsorption, Activated Carbon, Dirty Coal, Cadmium, Plumbum, Ion, Solution